Room at the Top - National Paint, Varnish (Pamphlets corresponding to radio shows produced by the National Paint, Varnish and Lacquer Association, 1940)
Booklet corresponding to a radio broadcast program created by the National Paint, Varnish, and Lacquer Association. The booklet describes how to remodel a home's attic to become a practical and useful space. Provides instructions for remodeling, and discusses several attic design choices to inspire the reader. Some options include converting the space into a guest room, a children's playroom, or a family den. Includes small stylized illustrations throughout and decorated covers. The National Paint, Oil and Varnish Association, Inc. was formed in 1933 and was the national professional association representing all branches of the paint, oil, and varnish industries.
Keywords: Attics; Paint materials; Interior decoration; Attics--Remodeling; Varnish and varnishing; Varnish industry; Paint industry and trade; Advertising--Paint